2011
DOI: 10.1002/adem.201080113
|View full text |Cite
|
Sign up to set email alerts
|

Superductile, Wavy Silica Nanostructures Inspired by Diatom Algae

Abstract: The interest in nanoscale biomimetics and biologically inspired designs for structural and mechanical applications has significantly increased over the past few years. One reason for this lies in the apparent benefits that come from nanomaterials, including enhanced mechanical properties and multifunctionality. Yet, many of these materials are produced from generally expensive methods with possible toxic byproducts. But what if we could harness the benefits of nanomaterials through efficient and environmentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Interdigitations are present throughout nature at interfaces such as those found in nacre (22,23), armored fish (24), algae (25), and sutures within the skull (26) and jaw (27). Interdigitations are believed to improve load transmission and increase energy absorption of the interfaces between bones in the skull (28).…”
Section: Introductionmentioning
confidence: 99%
“…Interdigitations are present throughout nature at interfaces such as those found in nacre (22,23), armored fish (24), algae (25), and sutures within the skull (26) and jaw (27). Interdigitations are believed to improve load transmission and increase energy absorption of the interfaces between bones in the skull (28).…”
Section: Introductionmentioning
confidence: 99%
“…Silica (SiO 2 ) is most commonly expressed within the biological materials of sponges and diatoms [76][77][78][79][80][81], and is generally found in its amorphous form [76][77][78][79]. The biomineralization of SiO 2 follows different processes in different organisms.…”
Section: Biomineralsmentioning
confidence: 99%
“…Several earlier studies have focused on studying these properties in light of their hierarchical nature [11][12][13][14][15][16]. With the advancement of computational tools, in silica studies have also become a popular tool used to gain fundamental insight into the design principles employed by nature in developing advanced materials from primitive building blocks [17][18][19][20][21][22]. In [17] it was shown that the nanometer size of certain structural features in mineralized structures might be selected to optimize local flaw tolerance.…”
Section: Introductionmentioning
confidence: 99%